Assessing the knowledge and awareness on crime among youth in Malaysia - Mohd Othman, Fazilah; Abdul Mutalib, Rozita; Arshad, Rozita; Ahmad, Zalinah (Future Academy, 2018)
In Malaysia, reducing crime is one of the efforts that had been outlined in the Government Transformation Program (GTP). Various policies and efforts have been implemented to minimize crime rate, for instance, the establishment of Malaysia Crime Prevention Foundation (MCPF) in 1993. However, reported crime rates are still high and cases of violent crimes are still escalating. Furthermore, the rate of crimes committed by youth has increased despite the decrease in the county’s overall crime index. This paper seeks to assess the level of youth knowledge and awareness on crime in Malaysia. A total of 953 sets of questionnaires were distributed among youth representatives, government agencies, non-governmental organization (NGOs) and Residential Committee. Data were analyzed using SPSS and presented through descriptive statistics related to the three research objectives. Results indicated that there is very little involvement in terms of crime prevention activities among youth. Although many still do not really understand the conducts that are considered as crime or otherwise, majority of the respondents were able to identify major crime acts such as killing, robbery and rape. The findings also revealed that youth dominantly obtained information through the social media and internet. Overall, there is a high sensitivity or awareness on crime. Hence, parental supervision, school counselling and involvement of enforcement agencies, besides community participation are significantly needed in addressing this problem.